Detection of the presence of bacteria causing grain rot disease (Burkholderia glumae) in some rice seed producers in South Sulawesi, Indonesia - Rahman, Abdul; Jahuddin, Rahmat; Bahar, Andi Khusnul Fatima; Yani, Ahmad; Patandjengi, Baharuddin (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2024)
One of the constraints in rice production is grain rot disease caused by Burkholderia glumae, which can be carried by seeds grain. An observation to determine the presence of B. glumae in different grain yield classes of seeds was conducted by taking samples derived from several seed producers in South Sulawesi. This research was carried out by first taking seed samples at the South Sulawesi Agricultural Technology Study Center (BPTP), Tungro Research Workshop, South Sulawesi Main Seed Center (Balai Benih Induk), PT. Sang Hyang Seri, PT. Pertani and PT. Harmoni were then tested at the Agricultural Quarantine Laboratory of Makassar. Based on the observations, it was concluded that all samples in the sowing seed class tested positive for B. glumae, supported by an average percentage of disease incidence of 25.13%, namely foundation seeds from the Balai Benih Induk, as well as foundation seeds and stock seeds from AIAT.